2022
DOI: 10.3389/fbuil.2022.705434
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Optimization Method for the Design of Active Hybrid Structures

Abstract: In structural engineering, active structures that combine the principles of lightweight construction with bending elastic component behavior are increasingly being investigated. For the realization of a prototype of an active hybrid roof structure at the laboratory of Hybrid Structures at BTU Cottbus-Senftenberg, preliminary investigations on a case study are conducted in the framework of this publication in order to improve the design process of these types of structures. These active hybrids require a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Based on previous investigations regarding energy efficient actuator placement for a similar structure, 8,12 we decided to realize a concept with actuation of the upper supports. This allows the actuators to be hidden inside the compression ring and the structure itself is kept simple and pure.…”
Section: Prototype Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous investigations regarding energy efficient actuator placement for a similar structure, 8,12 we decided to realize a concept with actuation of the upper supports. This allows the actuators to be hidden inside the compression ring and the structure itself is kept simple and pure.…”
Section: Prototype Conceptmentioning
confidence: 99%
“…46 Investigations conducted at our Chair showed that the Fin Ray ® structure allows a very energy-efficient transformation when actuated at the supports. 12…”
Section: Prototype Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research with a focus on structure control, actuation concepts, and actuator placement can be found for multi-story buildings [21][22][23][24][25], and also for shells [26], ribbedstiffened slabs [27], bridges [28,29], shear walls [30] and truss structures [31]. Standardized actuators that are available on the market have been used when a realization has taken place.…”
mentioning
confidence: 99%